PRE-HOSPITAL NURSING IN BASIC LIFE SUPPORT: ETHICAL AND LEGAL POSTULATES OF THE PROFESSION - Antônio César Ribeiro; Yanna Baralle Silva (Universidade Federal do Paraná, 2016)
The aim of this study was to discuss how nursing work is organized in pre-hospital care, considering the characterization of incidents assisted by a Basic Support Unit, observing the legislation that regulates this category's professional practice in Brazil. A descriptive, retrospective study conducted with the Emergency Mobile Care Service in Cuiabá, state of Mato Grosso. Data were gathered from the records of incidents from the first quarter of 2013. A total of 926 incidents were analyzed, and showed that injuries and nursing care are mostly of a complex nature, demanding technical and legal competencies for decision making, which takes us back to the necessary presence of a nurse. Thus, the model of organization of pre-hospital care, standardized by the Ministry of Health, is against the Brazilian nursing's legislation and workers who are technically responsible for nursing work or whose practice in nursing infringe upon the ethical and legal postulates of the profession.